Foundation walls - International Code Council ([Illinois] : International Code Council, 2006)
This video discuss basic requirements for foundation walls such as methods of construction, footing design, insulation and ventilation requirements
Title from title screen
DVD format
Keywords: Foundations; Concrete footings